Immunogenicity, Safety and Reactogenicity of a Booster Dose of the 10-Valent Pneumococcal Nontypeable H. influenzae Protein D Conjugate Vaccine Coadministered With DTPa-IPV-Hib in Dutch Children: A Randomized Controlled Trial. Issue 7 (July 2016) - van den Bergh, Menno R.; Spijkerman, Judith; François, Nancy; Swinnen, Kristien; Borys, Dorota; Schuerman, Lode; Veenhoven, Reinier H.; Sanders, Elisabeth A. M.
Abstract : Background: Immune responses and safety profiles may be affected when vaccines are coadministered. We evaluated the immunogenicity, safety and reactogenicity of a booster dose of the 10-valent pneumococcal nontypeable Haemophilus influenzae protein D-conjugate (PHiD-CV; Synflorix GSK Vaccines) and DTPa-IPV-Hib ( Pediacel Sanofi Pasteur MSD) when coadministered. Methods: We performed booster assessment in a randomized controlled trial in the Netherlands. Of 780 enrolled healthy infants, 774 toddlers participated in the booster phase and received (1:1:1) (1) PHiD-CV + DTPa-HBV-IPV/Hib ( Infanrix hexa, GSK Vaccines), (2) PHiD-CV + DTPa-IPV-Hib, or (3) 7-valent pneumococcal conjugate vaccine (7vCRM, Prevenar / Prevnar, Pfizer, Inc.) + DTPa-IPV-Hib at 2, 3, 4 and 11–13 months old. Blood samples were taken postprimary, prebooster, 1 and 12 months postbooster. Results: Antipneumococcal antibody responses were comparable between both PHiD-CV groups, except for serotype 18C (conjugated to tetanus toxoid). Anti-18C antibody geometric mean concentrations (GMCs) were higher when coadministered with DTPa-HBV-IPV/Hib. For each vaccine serotype, the percentages of children with antibody concentration ≥ 0.20 μg/mL were within the same ranges between PHiD-CV groups (93.8%–100%). The same was observed for the percentages of participants with opsonophagocytic activity titer ≥ 8 (90.9%–100%). When comparing both DTPa-IPV-Hib groups, postbooster antidiphtheria antibody GMCs were higher when coadministered with 7vCRM, while antitetanus and antipolyribosyl-ribitol phosphate antibody GMCs were higher with PHiD-CV coadministration. Regardless, antibody levels to these antigens were well above thresholds. Safety and reactogenicity profiles were comparable between groups. Conclusions: Coadministration of a booster dose of PHiD-CV and DTPa-IPV-Hib was immunogenic and well tolerated.